2013
DOI: 10.5539/jmsr.v2n2p51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Strain Life of Aluminum Alloy AA 6061

Abstract: The present work encompasses the investigation of Low Cycle Fatigue (LCF) of aluminum alloy AA6061 in three conditions, annealing (O), T4 and T651. AA6061-O has the higher value of transition fatigue life (N T ) because it has the highest ductility, while the fatigue strength exponent and fatigue ductility exponent are within the range of metallic materials. The SEM morphology for specimens at strain closer to true tensile stress show multi-crack origins with secondary cracks and large final fracture zone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
2
15
0
1
Order By: Relevance
“…The 6xxx-series aluminum alloys are extensively used in the aerospace and automotive industries, owing to their ideal mechanical properties, good corrosion resistance, as well as good formability and weldability [1][2][3][4]. There is considerable industrial interest in these alloys, as two thirds of all extruded products are made of aluminum, and 90% of these are made of the 6xxx-series alloys [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6xxx-series aluminum alloys are extensively used in the aerospace and automotive industries, owing to their ideal mechanical properties, good corrosion resistance, as well as good formability and weldability [1][2][3][4]. There is considerable industrial interest in these alloys, as two thirds of all extruded products are made of aluminum, and 90% of these are made of the 6xxx-series alloys [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable industrial interest in these alloys, as two thirds of all extruded products are made of aluminum, and 90% of these are made of the 6xxx-series alloys [4]. AA6061 alloys are one of the most widely used precipitation-hardening aluminum alloys in the 6xxx series [2,3,5]. Structural components of AA6061 alloys used in engineering services would require the evaluation of their mechanical performance under cyclic loads, because these components would unavoidably experience dynamic loading in service, which leads to the occurrence of fatigue failure [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In case of Al alloys, significant improvements in low cycle fatigue [5] and high cycle fatigue [3] were reported by employing shot peening at optimized parameters. K. A. Soady et al [6] investigated the effect of shot peening on notched low cycle fatigue of heat resistant alloy and revealed substantial improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium alloys have become important materials for space, military, automobile and various commercial applications due to their higher specific strength, low density and specific modulus apart from adequate fracture and fatigue resistance. A few attempts have been made in the past to study deformation behaviour of aluminium alloys for sheet metal applications [1][2][3]. Earlier studies also reported formability characteristics and forming limits of the AA 2014 automotive aluminium sheets [4,5].…”
Section: Introductionmentioning
confidence: 99%